Capitalist racionality and economic principle - Reuben Soto, Sergio (2021)
In this article we subject the concept of "rationality" to scrutiny, as an exercise in reason. As we advanced in the investigation, it became clear that this reason is based on a set of values ​​and principles that validate our actions based on that reason as correct decisions. In this way we saw the need to distinguish between instrumental reason and communicative reason as proposed by Habermas, in order to understand that this instrumental reason is validated with the intention of reaching the "economic principle". And we conclude that this instrumental reason is determined by the historical conditions in which society finds itself.  Thus, we proposed a capitalist instrumental reason or capitalist rationality as the reason that guides the set of economic actions that are taken within the framework of a society determined by the accumulation of capital with the aim of achieving the economic principle. Hence what was done was to confront this rationality with its ability to achieve the economic principle, in the historical conditions of its development.